Digital Storytelling in a Flipped Classroom for Effective Learning - Clemens Bechter; Fredric W. Swierczek (MDPI AG, 2017)
Conclusive empirical evidence on whether virtual classrooms result in higher performance, satisfaction, or an improvement in problem solving skills when compared with traditional face-to-face lecturing does not exist. Various studies point in different directions. However, blended learning outperforms the traditional classroom in student performance and satisfaction. A flipped classroom is one type of blended learning. For more than 20 years, this approach has been used at a European executive MBA (EMBA) program delivering online content combined with six residential weeks where students collaborate and reflect upon their online learning. Our research examined the overall setup of this program, and assessed one course in depth. As part of the course-International Management-an intercultural negotiation project was chosen to highlight the integration of online and offline activities. The flipped classroom is a demonstration of the reform-based teaching approach. The power of reform-based learning in executive education is the engaging combination of practice and theory, which improves the performance of executives. The participants considered the flipped approach exciting, dynamic, and insightful. The emphasis on a negotiation process involving classmates from around the world increased their global understanding. Beginning with a negotiation experience in the digital story project gave them a better appreciation of the relevant theories, techniques, and applications. Focusing on the practice of international negotiation and a cross-cultural analysis with reflection on cultural intelligence improved the competencies of the participants both during the course and after it.